Blood Pressure in a Large Cohort of Children and Adolescents With Classic Adrenal Hyperplasia (CAH) Due to 21-Hydroxylase Deficiency - Bonfig, Walter; Roehl, Friedrich-Wilhelm; Riedl, Stefan; Dörr, Helmuth-Günther; Bettendorf, Markus; Braemswig, Juergen; Schoenau, Eckhard; Riepe, Felix; Hauffa, Berthold; Holl, Reinhard W.; Mohnike, Klaus (American Journal of Hypertension, 2016)
BACKGROUND: Data on blood pressure (BP) in children and adolescents with classic congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency are conflicting in the literature. PATIENTS AND METHODS: BP data of n = 716 children and adolescents (aged 3-18 years) from a national CAH database were analyzed. BP data were adjusted for height and compared to contemporary national reference data. A systolic and diastolic BP above the 95th centile was defined as hypertensive. RESULTS: Overall prevalence of hypertension was 12.5%. Prevalence of hypertension was higher in younger children than in adolescents (18.5% vs. 4.9%). Until 8 years of age, fludrocortisone dose/m(2)/day correlated significantly with BP in regression analysis (P < 0.0001). BP correlated significantly with body mass index standard deviation score (BMI-SDS) (P < 0.0001), but not with hydrocortisone dose. In patients with salt-wasting CAH, BMI-SDS and BP were significantly higher compared to patients with simple virilising CAH, P < 0.01. CONCLUSION: Especially young CAH children seem to be at risk for-most likely transient-hypertension, since the prevalence of hypertension decreases with age. In children up to 8 years of age, the used fludrocortisone dose is a significant risk factor for hypertension. Therefore we recommend accurate measurement of BP and careful fludrocortisone dosing in children with CAH.
EVALuna2:34016